CONCEPT ANALYSIS OF SELF-MANAGEMENT IN PATIENT WITH DIABETES NEPHROPATHY - Dayan Hisni; Pradana Soewondo; Debie Dahlia; Dian Ayubi (LLDIKTI Wilayah X, 2023)
ABSTRACT Diabetes mellitus (DM) is a metabolic disease with characterized by hyperglycemia and it has some complications both macrovascular and microvascular. There have been reported that 40% of DM patient has developed diabetic nephropathy (DN) in the early of diagnosed. Therefore, some nursing intervention should be done to prevent DM including DN. One of them is self-management. This article aims to explain the concept of self-management to prevent DN in patient with DM. The method used is the Walker and Avant concept approach. The Walker and Avant framework clarifies current self-management understanding and use in practice and research across multiple disciplines. This concept’s critical attributes include personal skills, self-management, lifetime task, problem solving in health area, and decision making properly. The conclusion of this analysis concept is to increase nurses’ knowledge regarding self-management in patient with DN.